Photochemical Generation and Reactivity of the 5,6-Dihydrouridin-6-yl Radical - Newman, Cory A. (J Org Chem, 2009)
Nucleobase radicals are the major family of reactive intermediates formed when nucleic acids are exposed to hydroxyl radical, which is produced by γ-radiolysis and Fe • EDTA. Significant advances have been made in understanding the role of nucleobase radicals in oxidative DNA damage by independently generating these species from photochemical precursors. However, this approach has been used much less frequently to study RNA molecules. Norrish type I photocleavage of the tert-butyl ketone (2b) enabled studying the reactivity of 5′-benzoyl-5,6-dihydrouridin-6-yl (1b). High mass balances were observed under aerobic or anaerobic conditions, and O(2) did not affect the photochemical conversion of the ketone (2b) to 1b. Competition studies with O(2) indicate that the radical abstracts hydrogen atoms from β-mercaptoethanol with a bimolecular rate constant = 2.6 ± 0.5 × 10(6) M(−1)s(−1). The major product formed in the presence of O(2) was 5′-benzoyl-6-hydroxy-5,6-dihydrouridine (6). In contrast, 5-benzoyl-ribonolactone (7), a hypothetical product resulting from C1′-hydrogen atom abstraction by the peroxyl radical, could not be detected. Overall, tert-butyl ketone 2b is a clean source of 5′-benzoyl-5,6-dihydrouridin-6-yl (1b) and should prove useful for studying the reactivity of the respective radical in RNA.